A putative transport protein is involved in citrulline excretion and re-uptake during arginine deiminase pathway activity by Lactobacillus sakei - Rimaux, Tom (2013)
Arginine conversion through the arginine deiminase (ADI) pathway is a common metabolic trait of Lactobacillus sakei which is ascribed to an arc operon and which inquisitively involves citrulline excretion and re-uptake. The aim of this study was to verify whether a putative transport protein (encoded by the PTP gene) plays a role in citrulline-into-ornithine conversion by L. sakei strains. This was achieved through a combination of fermentation experiments, gene expression analysis via quantitative real-time reverse transcription PCR (RT-qPCR) and construction of a PTP knock-out mutant. Expression of the PTP gene was modulated by environmental pH and was highest in the endexponential or mid-exponential growth phase for L. sakei strains CTC 494 and 23K, respectively. In contrast to known genes of the arc operon, the PTP gene showed low expression at pH 7.0, in agreement with the finding that citrulline-into-ornithine conversion is inhibited at this pH. The presence of additional energy sources also influenced ADI pathway activity, in particular by decreasing citrulline-into-ornithine conversion. Further insight into the functionality of the PTP gene was obtained with a knock-out mutant of L. sakei CTC 494 impaired in the PTP gene, which displayed inhibition in its ability to convert extracellular citrulline into ornithine. In conclusion, results indicated that the PTP gene may putatively encode a citrulline/ornithine antiporter.